RFID Mobile Ticketing System - Chong, Charles Aik Hun (2004)
In this thesis, a RFID (Radio Frequency Identification) module is interfaced with a personal computer and a GSM (Global System for Mobile Communications) modem to implement RFID Mobile Ticketing System. RFID Mobile Ticketing System allows mobile phone user to purchase tickets using their mobile phone and RFID ticket.